Now you see me 2 [videorecording (DVD)] - Eisenberg, Jesse, 1983-; Radcliffe, Daniel, 1989-; Ruffalo, Mark; Harrelson, Woody; Caine, Michael; Freeman, Morgan (Summit Entertainment/Lionsgate, 2016)
One year after outwitting the FBI and winning the public's adulation with their Robin Hood-style magic spectacles, The Four Horsemen resurface for a comeback performance in hopes of exposing the unethical practices of a tech magnate. The man behind their vanishing act is none other than Walter Mabry, a tech prodigy who threatens the Horsemen into pulling off their most impossible heist yet.